The Wicked Problem of Scholarly Impact. Issue 4 (22nd November 2017) - Behrend, Tara; Landers, Richard
Abstract : Academics sometimes forget that the purpose of a university is to educate : our students, our local communities, each other, and the world. Although each university is unique in its constituency, all share the charge to generate knowledge for the protection and benefit of the public good. The goal of an academic should be to beneficially impact society, broadly defined, with scholarly activity. As editor and columnist for The Industrial-Organizational Psychologist, one publication highlighted by the focal article, we applaud the efforts of Aguinis et al. (2017 ) to put forth alternative approaches to defining impact. Like them, we are concerned that many of the measures of "impact" we currently use do not capture this charge.